Sr-doped yttrium nickel oxide-based photodetectors - Yalcin, Mesut; Ozmen, Denizhan; Yakuphanoğlu, Fahrettin (Springer, 2020)
In this research, Sr-doped yttrium nickel oxide-based photodetectors have been fabricated. The electrical properties of diodes have been analyzed by using Cheung and Norde methods. The ideality factors, barrier heights, and series resistances of diodes have been calculated under visible light at different irradiation intensities. In addition, the photoresponse behavior of photodetectors was investigated under visible light at different irradiation intensities. The highest responsivity (R) and detectivity (D*) were calculated as 25.34 mA/W and 7 x 84 10(11) Jones, respectively. These results suggest that the photodetectors can be used optoelectronic device applications.
Keywords: Photovoltaic Properties; Nio Nanoparticles; Spectral Response; Interface States; High-Detectivity; Current-Voltage; Diode; Heterojunction; Photodiodes; Performance